Kegiatan Berbasis Pengabdian Masyarakat Bidang Pendidikan Di Pesantren Al-Fath Melalui Pelatihan Jawa Pegon Dalam Upaya Memaknai Kitab Kuning - Izuddi Niyah; Nurmahmudah Nurmahmudah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Islamic boarding schools are divided two, salaf and modern Islamic boarding schools. One of the activities of the Pesantren is reciting the yellow book. Translating or interpreting the yellow book in Arabic into Javanese using Pegon. The purpose of writing this article is to improve the ability of students in interpreting the yellow book at the Al-Fath Islamic boarding schools by using the Pegon letter as a translation of a word in the yellow book. The obstacle experienced is the lack of knowledge and ability of the students in the interpreting the yellow book, so that students experience difficulyies in Islamic boarding school activities programs such as reciting the yellow book using Pegon letters. The service team from IAIN Kediri collaborated and colsulted with related parties to provide solutions through training and development of Pegon activity programs for students to improve the ability of students to interpreting the yellow book in Islamic boarding schools correctly and quickly. Community service activities for students are carried out at the Al-Fath Islamic boarding school. Participants who take part in service program are new students of the Al-Fath Islamic boarding school. The activities contribute to Islamic boarding schools and students. For Islamic boarding school, Islamic boarding schools have a place as a means of Pegon learning activities to interpreting the yellow book. As for the students, increasing knowledge and ability in interpreting the yellow book using Pegon letters precisely and quickly